ADAPTATION OF A YOUNG SPECIALIST TO PROFESSIONAL ACTIVITY - kobal, Vasyl; Rozman Ірина (Mountain School of Ukrainian Carpaty, 2025)
The article focuses on ways of adapting a young specialist to pedagogical professional activity. It is noted that the true formation of a teacher occurs with the beginning of professional activity. Only in the classroom does a young teacher understand whether this is his vocation or whether he wants to devote his life to it. Emphasis is placed on the importance of mutual visits for improving the teacher's skills. A young teacher has the opportunity to enrich his teaching experience and plan his professional growth. The goal of collective forms of methodological work is to improve the skills of all teachers in the process of purposefully planned and implemented activities. It is emphasized that the most common collective forms of methodical work in an institution of general secondary education are open lessons. The purpose of the article is a theoretical justification of the importance of forming pedagogical conditions for the professional self-development of future teachers and determining the level of professional training of future teachers for practical activities. Also, in addition to improving professional growth, there are ways to improve the methodical training of the teacher and the adaptation capabilities of the specialist to professional activity. It was noted that the subject methodical associations of teachers, as centers of methodical work, have an extremely important function of adapting young specialists. Four components of one's own «I» and specific stages of formation of a teacher's professional competence are singled out. It is emphasized that an effective form of self-improvement is imaginary entry into the role of an experienced colleague. But using the experience of others carries the threat of inhibiting one's own initiatives and creativity. Therefore, it is necessary to solve a number of issues: conduct a diagnosis of the work of a young teacher; to promote the study of regulatory and legal documents on education; to improve educational and methodical training of modern teachers; promote the mastery of innovative technologies, advanced methods of teaching and education; to encourage the study and application of best practices in pedagogy. During the adaptation period of a young specialist in an educational institution, special attention should be paid to the level of methodical work. They will be divided into three: school level, city level, regional level. It is noted that in order to improve the professional training of pedagogical personnel in schools, special methodical work is carried out, which encourages teachers to improve their qualifications, contributes to the mutual enrichment of the pedagogical team with pedagogical experience, enables young teachers to learn pedagogical skills from experienced colleagues, ensures the desire of the pedagogical team to find new ones forms and methods of work.